Progress on Multifunction Enzyme-Activated Organic Fluorescent Probes for Bioimaging - Lian, Jie; Wang, Yipeng; Sun, Xiaomeng; Shi, Quanshi; Meng, Fanda (Frontiers in Chemistry, 2022)
Bioimaging techniques are of increasing importance in clinical and related fields, which also have been successfully applied in vivo/in vitro imaging system. Due to the vital factor of enzymes in biological systems, enzyme activated fluorophores, which could turn “on” the fluorescence signal from an “off” state, offer non-invasive and effective potential for the accurate bioimaging of particular cells, tissues or bacteria. Comparing with the traditional imaging probes, enzyme activated organic small fluorophores can visualize living cells within small animals with high sensitivity, high imaging resolution, noninvasiveness and real-time feedback. In this mini review, well-designed enzyme activated organic fluorescent probes with multiple functions are exclusively reviewed through the latest development and progress, focusing on probes design strategy, fluorescence property, enzyme activation process and bioimaging applications. It is worth noting that multi-enzyme activated strategies, which could avoid the production of ''false positive'’ signals in complex biological systems, effectively provide high selective and real-time bioimaging, indicating the exciting potential of intraoperative fluorescence imaging and diagnosis tools.